Spatial Planning Systems in Western Europe : an Overview. - Larsson, G. (Stand alone / stal, 2006)
Presents information on how different countries within the chosen area have tried to solve the problem of establishing suitable systems of steering spatial development by means of planning and implementation measures. This book provides an overview of the systems in Western Europe, how they have influenced each other.